2018
DOI: 10.3892/ol.2018.9752
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‑delivered TRPP2 siRNA inhibits the epithelial‑mesenchymal transition of FaDu cells

Abstract: The prognosis for patients with head and neck cancer (HNC) remains poor, owing to uncontrolled tumor invasion and metastasis. Epithelial-mesenchymal transition (EMT) serves an important role in this invasion and metastasis, and transient receptor potential polycystic 2 (TRPP2) enhances metastasis and invasion by regulating EMT in human laryngeal squamous cell carcinoma. The present study examined whether exosomes/TRPP2 small interfering RNA (siRNA) complexes were able to reduce EMT by suppressing TRPP2 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Furthermore, Snail , an EMT transcriptional factor, was shown to activate the M1 macrophage- (M1 M Ф -) M2 macrophage (M2 M Ф ) transition by increasing TDEs-miR-21 and transferring TDEs to CD14 + human monocytes, which promotes the advancement of HNC [67]. Therefore, the import of exosomal siRNAs into tumor cells may be an effective tumor gene and immunotherapy method to suppress the expression of target mRNAs [68]. Interestingly, the impact of exosomes on EMT is not completely one-sided.…”
Section: The Function Of Exosomes In the Tumor Microenvironment Anmentioning
confidence: 99%
“…Furthermore, Snail , an EMT transcriptional factor, was shown to activate the M1 macrophage- (M1 M Ф -) M2 macrophage (M2 M Ф ) transition by increasing TDEs-miR-21 and transferring TDEs to CD14 + human monocytes, which promotes the advancement of HNC [67]. Therefore, the import of exosomal siRNAs into tumor cells may be an effective tumor gene and immunotherapy method to suppress the expression of target mRNAs [68]. Interestingly, the impact of exosomes on EMT is not completely one-sided.…”
Section: The Function Of Exosomes In the Tumor Microenvironment Anmentioning
confidence: 99%
“…[25] In line with Wang's discovery, exosomes/TRPP2 siRNA complex is capable of suppressing TRPP2 expression of Fadu cells, meanwhile, low expression of TRPP2 elicits an increase in E-cadherin, but downward expression levels of N-cadherin and vimentin. [26] Reports have revealed that rehabilitation of SCI rats achieved satisfactory results via injecting intravenously with exosomes (control exosomes, miRNA-29b exosomes) and BMSCs (miR NC, miRNA-29b) to the tail vein. [27] Li has suggested that exosomes derived from miR-544 modi ed BMSCs exhibited a protective role for the SCI rat model in improving their functional recovery as well as the promotion of neuronal survival.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting precipitate was the EPC-derived exosomes. 12 The concentration of the EPC-derived exosomes was determined using a BCA protein concentration assay. Isolated exosomes were stored at −80°C for 1 month.…”
Section: Separation and Identification Of Epc-derived Exosomesmentioning
confidence: 99%